Legal Protection of Female Workers Through Marriage Agreements In Ponorogo Regency - Dody Syahrul Irawan; Abdul Rachmad Budiono; Rachmi Sulistyarini (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Ponorogo Regency is one of the regions sending a significant number of female migrant workers (TKW), reaching 30,793 in the 2022–2024 period. The high number of Indonesian migrant workers (PMI) is correlated with the increase in divorce cases at the Ponorogo Religious Court, particularly divorce cases filed by wives. This situation raises legal issues, particularly regarding the division of joint assets, which often disadvantage migrant workers as the economically dominant party during the marriage. This study aims to analyze the urgency of a prenuptial agreement as an instrument of legal protection for migrant workers from a notarial law perspective. The research method used is empirical juridical with a statutory approach and field interviews. Normatively, the provisions of Law Number 1 of 1974 concerning Marriage, which were expanded through Constitutional Court Decision Number 69/PUU-XIII/2015, have provided legal space for couples to enter into a prenuptial agreement before and during the marriage. However, research results indicate that the implementation of prenuptial agreements in Ponorogo remains low due to limited legal literacy, inadequate outreach, and cultural barriers that view such agreements as a sign of mistrust. Therefore, prenuptial agreements are urgently needed as a preventative measure to ensure legal certainty, justice, and the protection of migrant workers' assets, as well as to minimize joint property disputes in divorce. (Law No. 1 of 1974).